SYSTEMATIC REVIEW OF SAR REDUCTION TECHNIQUES FOR MINIMIZING MOBILE PHONE RADIATION - Rajan, S.Palanivel; Vivek, C. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this mobile digital world cellular handsets and tablet pc’s have become the common used devices .These devices use the Electromagnetic Frequency (EMF) Spectrum which is wide spread in our atmosphere. Electromagnetic fields of all frequencies represent one of the most common and fastest growing environmental influences, about which anxiety and speculation are spreading. All populations are now exposed to varying degrees of EMF, and the levels will continue to increase as technology advances. The World Health Organization (WHO) established the International EMF Project in 1996 to assess the scientific evidence of possible health effects of EMF in the frequency range from 0 to 300 GHz and possibly reducing the effects caused by them. Our project aims in limiting the hazardous EM radiation emitted from the mobile phones. This can be achieved by using the PIFA antenna in the Transfer electromagnetic (TEM) cell experimental setup